2014
DOI: 10.1111/bjd.12812
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ/CCR5 expression in invariant natural killer T cells and CCL5 expression in capillary veins of dermal papillae correlate with development of psoriasis vulgaris

Abstract: IFN-γ/CCR5 expression in iNKT cells and CCL5 expression in vessels of dermal papillae correlate with the development of psoriasiform hyperplasia and microabscess. We propose that these iNKT cells may become useful targets for development of novel therapeutic approaches to PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Several of them have been identified to be associated with the incidence and development of psoriasis. Kono et al (18) reported that the expression of CCR5 and CCL5 was associated with the development of psoriasiform hyperplasia and microabscess. Also, through managing multiple chemokines, keratinocytes actively participate in the inflammatory response in psoriasis patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several of them have been identified to be associated with the incidence and development of psoriasis. Kono et al (18) reported that the expression of CCR5 and CCL5 was associated with the development of psoriasiform hyperplasia and microabscess. Also, through managing multiple chemokines, keratinocytes actively participate in the inflammatory response in psoriasis patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Th1 immune response is another possible pathway in the triggering of plaque psoriasis. IL-12 is a potent inducer of the Th1 differentiation with naïve lymphocytes becoming IFN-γ-producing cells [ 25 , 26 ]. Our results showed that imiquimod did not increase IL-12 and IFN-γ in mouse skin.…”
Section: Discussionmentioning
confidence: 99%
“…iNKT cells have been implicated as playing roles in infection control [11,12], inflammatory bowel diseases [13], abortion [14], transplantation tolerance [15,16], suppression of autoimmune diseases [17][18][19][20], psoriasis and atopic dermatitis [21], and the regulation of allergic disorders [22,23]. iNKT cells have the potential to activate or suppresses immune system by release of variable cytokines including IFN-γ, IL-4, IL-10, and IL-17.…”
Section: Invariant Natural Killer T (Inkt) Cells In Diseasesmentioning
confidence: 99%
“…where the perimeter (P) of individual cells was divided by the circumference of a circle with the same area (A), with the real circle factor being equivalent to 1.0. As the boundary of a binary image is composed of discrete pixels, IMAQ Vision (National Instruments Corporation, Austin, TX, USA) was used to sub-sample the boundary [21,39]. The scheme of quantitative morphometry is shown below.…”
Section: Quantitative Morphometrymentioning
confidence: 99%